Complete genome sequences of novel Berlinvirus and novel Certrevirus lytic for Pectobacterium sp. causing soft rot and black leg disease of potato - Petrzik, Karel; Kmoch, Martin; Brázdová, Sára; Ševčík, Rudolf (Virus genes, 2021)
Two novel dsDNA bacteriophages named Pectobacterium virus CB251 (PcCB251) and Pectobacterium virus CB7V (PcCB7V) targeting plant pathogen Pectobacterium parmentieri have been isolated and sequenced. The PcCB251 genome consists of 40,557 bp with G+C content of 48.6% and contains 47 predicted genes on a single strand. The phage is classified in genus Berlinvirus, family Autographiviridae. The PcCB7V phage has a circular dsDNA genome of 146,054 bp with G+C content of 50.4% and contains 269 predicted protein genes on both strands and 13 tRNA genes. The PcCB7V phage can be classified in genus Certrevirus, subfamily Vequintavirinae. Both novel bacteriophages have narrow host ranges, but they extend the list of candidates for phage-based control of pectolytic bacteria causing soft rot disease of potato.
Keywords: Complete sequence; genom virový; Berlinvirus; Certrevirus; Soft rot of potato; Solanum tuberosum; Genome, Viral; sekvenování celého genomu; Plant Viruses; Bacteriophages; DNA Viruses; DNA viry; bakteriofágy; Novel virus; rostlinné viry; Whole Genome Sequencing; Pectobacterium